The use of PROMs and shared decision‐making in medical encounters with patients: An opportunity to deliver value‐based health care to patients - Damman, Olga C.; Jani, Anant; Jong, Brigit A.; Becker, Annemarie; Metz, Margot J.; Bruijne, Martine C.; Timmermans, Danielle R.; Cornel, Martina C.; Ubbink, Dirk T.; Steen, Marije; Gray, Muir; El, Carla (Journal of evaluation in clinical practice, 2020)
Background The recent emphasis on value‐based health care (VBHC) is thought to provide new opportunities for shared decision‐making (SDM) in the Netherlands, especially when using patient‐reported outcome measures (PROMs) in routine medical encounters. It is still largely unclear about how PROMs could be linked to SDM and what we expect from clinicians in this respect. Aim To describe approaches and lessons learned in the fields of SDM and VBHC implementation that converge in using PROMs in medical encounters. Approach Based on input from three Dutch forerunner case examples and available evidence about SDM and VBHC, we describe barriers and facilitators regarding the use of PROMs and SDM in the medical encounter. Barriers and facilitators were structured according to a conversational model that included monitoring and managing, team talk, option talk, choice talk, and decision talk. Key lessons learned and recommendations were synthesized. Results The use of individual, N = 1 PROMs scores in the medical encounter has been largely achieved in the forerunner projects. Conversation on monitoring and managing is relatively well implemented, and option talk to some extent, unlike team talk, and decision talk. Aggregated PROMs information describing outcomes of treatment options seemed to be scarcely used. Experienced barriers largely corresponded to what is known from the literature, eg, perceived lack of time and lack of tools summarizing the options. Some concerns were identified about increasing health care consumption as a result of using PROMs and SDM in the medical encounter. Conclusion Successful implementation of SDM within VBHC initiatives may not be self‐evident, even though individual, N = 1 PROMs scores are being used in the medical encounter. Education and staff resources on meso and macro levels may facilitate the more time‐consuming SDM aspects. It seems fruitful to especially target team talk and choice talk in redesigning clinical pathways.